Efek Mediasi Motivasi Atas Hubungan Etos Kerja Terhadap Kinerja Pegawai Dinas Kehutanan UPT. Kesatuan Pengelolaan Hutan Wilayah II Pematangsiantar - Marthin Hutler Ambarita; Sudung Simatupang; Vivi Candra (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
The purpose of this study was to determine the description of motivation, work ethic and employee performance at the Forest Service Unit of UPT. Forest Management Unit Region II Pematangsiantar and to determine the effect of motivation on the relationship of work ethic on employee performance at the Forest Service Unit of UPT. Forest Management Unit Region II Pematangsiantar. This research uses the design of library research and field research. The population in this study were UPT Forest Service employees. The Pematangsiantar Region II Forest Management Unit totaling 67 employees. The type of data used is qualitative and quantitative data. Data sources used are primary data and secondary data. Data collection is done by questionnaire, interview and documentation. The analysis technique used is the classic assumption test with validity, reliability and normality tests, qualitative descriptive analysis and quantitative descriptive analysis with path analysis and hypothesis testing. The results of the study concluded that the work ethic has a significant effect on employee performance. Motivation has a significant effect on employee performance and motivation is able to mediate the relationship of work ethics on employee performance.